TRANSFORMASI ETIKA DIGITAL: MEMBANGUN KEWARGAAN DIGITAL KRITIS (CRITICAL DIGITAL CITIZENSHIP) DI TENGAH HEGEMONI ALGORITMA - Marina Rospitasari; Lailatus Sholihah; Dyah Ayu Kusuma Dewandaru; Wahidah R Bulan; Daffa Rakha Wijaya (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2026)
The rapid penetration of digital technology, modern society faces an interaction paradox: massive technical connectivity accompanied by increasingly sharp social polarization. This article aims to dissect the failure of conventional digital ethics approaches, which tend to be normative and technical, and offers the Critical Digital Citizenship model as an adaptive solution amidst algorithmic hegemony. Employing a conceptual literature review method, this study synthesizes Mike Ribble's concept of digital citizenship with Paulo Freire's critical pedagogy. The analysis reveals the existence of an